Effectiveness of Project Work in Free Writing: A True Experimental Research - Tiwari, Hari Prasad (KMC Journal, 2024)
Project work is a pedagogical technique which engages students in collaborative and authentic tasks. However, there is a lack of empirical evidence on how project work learning influences students' ability to write spontaneously and fluently on any given topic. The purpose of this study was to examine the effect of project work in teaching free writing skill for grade ten students. The study employed true experimental design. The researcher used convenience sampling to select one of the community schools of Banke district as the site of the study and typical case sampling to select the class. From the selected class, the researcher chose 60 students as the sample using simple random sampling. A randomization technique was used to divide the sample into two equal groups of 30 students each and the groups were labeled as Control Group (CG) and Experimental Group (EG). He used test as the technique to collect the data. Both groups were tested on ten free writing questions before and after 30-day intervention period. The data were analyzed using descriptive and inferential statistics namely variance, standard deviation, and ‘t’ tests. The findings revealed that the EG improved significantly than the CG in their free writing skills. The average score of the EG increased by 31.40 %, while the CG increased by only 6.69 %. The results indicate that project work learning can enhance free writing skills of grade ten students and recommends its use as a pedagogical strategy for enhancing writing proficiency.